Strengthening the effectiveness of accounting information systems: A systematic review of AI integration and internal control practices - Hastuti, Diana Asmi; Widuri, Rindang (Edelweiss Applied Science and Technology, 2025)
This paper examines how the integration of artificial intelligence (AI) and internal control practices contributes to the effectiveness of accounting information systems (AIS) in the context of digital transformation. This study conducts a systematic review of AI integration and internal control practices in strengthening AIS effectiveness. Employing the Systematic Literature Review (SLR) method aligned with PRISMA 2020 guidelines, 97 international scientific articles published between 2019 and 2025 were analyzed from the Scopus database. The review demonstrates that AI adoption consistently enhances efficiency, automation, and analytical capabilities in AIS, while internal controls remain crucial for ensuring reliability, accountability, and mitigation of information risks. The analysis highlights the mediating role of accounting information quality in linking AI, internal controls, and AIS effectiveness; nonetheless, it also raises unresolved challenges. The study emphasizes the importance of balancing technological innovation with robust governance for managers, auditors, and policymakers on investing in digital capabilities, strengthening internal control frameworks, and establishing governance policies that promote the responsible adoption of AI in accounting practices.